Implementation of Data-Based Regional Development Planning and Public Participation in The Regional Development Planning Agency (Bappeda) of Sidoarjo Regency - Jhoni Arwan S; Ika Devy Prmudiana; Amirul Mustofa (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2025)
This research investigates the execution of data-informed and inclusive regional development planning within the Regional Development Planning Agency (Bappeda) of Sidoarjo Regency, concentrating on four analytical aspects: data integration and management abilities, the efficiency of participatory processes, technical and institutional obstacles concerning interoperability, and capacity-building strategies for facilitators tasked with translating public aspirations into planning priorities. The study is positioned within the national framework to establish evidence-based and participatory planning in reaction to the growing complexity regional development. Despite Bappeda Sidoarjo implementing multiple data platforms and participatory channels such Musrenbang forums, online submission systems, and sector-specific information systems the results indicate that issues like data fragmentation, insufficient digital literacy, and ineffective follow-up mechanisms continue to impede planning effectiveness. Employing qualitative methodology that includes in-depth interviews, observation, and document review, the research reveals that data integration has not reached single source of truth because of the lack of a cohesive data architecture and compatible standards among government entities. Participatory methods have increased inclusivity, but the quality of proposals and verification processes is still variable, hindering the incorporation of grassroots feedback into planning priorities. Moreover, the ability of facilitators the subdistrict and village levels is crucial in determining the quality of the compiled proposals. The research ends by highlighting the importance of improved data governance, increased actor capability, revised participatory processes, and clear follow-up mechanisms. Suggestions encompass constructing a unified data framework, offering ongoing technical training, standardizing digital Musrenbang processes, and establishing publicly available proposal-tracking system integrated within the yearly planning cycle.